KONSEP KEPEMILIKAN ASSET TETAP DALAM AKUNTANSI SYARIAH (Jurnal Akuntansi, 2018)
Allah SWT is the absolute owner of property as explained in the Qur'an An-Nisa, 132 explains: "And belongs to God what is in the sky and on earth". Then in the Surah Al-Baqarah verse 29 it says: "He is Allah, Who made everything on earth for you." Treasures owned by humans are entrusted by Allah SWT and ownership and use of property by individuals are limited. Whereas conventional ownership of property is unlimited and is only limited by laws and moral ethics in its use. Capra (2001: 26) says that in Islam there is no separation between material (world) and spiritual life ("in spite of its emphasis on morals, Islam does not recognize any watertight distinction between the material and the spiritual"). In that sense it can be concluded that sharia accounting is part of spiritual Islam itself. So it can be interpreted as ownership of assets in sharia accounting following the system of rules that apply in Islamic sharia itself. Recording and reporting of fixed assets in sharia accounting must follow the established sharia method and will be discussed in this article. Includes zakat on fixed assets of the company.